EFEKTIVITAS PEMBERIAN AROMATERAPI LAVENDER DENGAN PENURUNAN TINGKAT KECEMASAN : LITERATURE REVIEW - Sri Nyumirah; Lucia Firsty Puspita Krishna (Universitas Karya Husada Semarang, 2025)
Introduction: Anxiety is a psychosocial problem that often occurs in a person. Ansietas is ranked 2nd according to Riskesdas data in 2018, the prevalence of anxiety that occurs from 14 million people in Indonesia experiencing emotional mental disorders is characterized by symptoms of anxiety or 6% experiencing anxiety. A person who experiences anxiety will have an impact on the individual against threats to physical integrity that affect the decline in daily activities. The impact that occurs will affect the components of self-concept and ability to interact socially. Curative efforts that can be made as a nurse in reducing anxiety that occurs with non-pharmacological therapy. The therapy carried out can be the application of complementary therapy, one of the therapies applied to reduce anxiety with the use of lavender aromatherapy. Objective: To analyze the effectiveness of lavender aromatherapy on reducing anxiety levels. Method: literature review study yesKey words: aromatherapy, lavender, the level of anxiety. Method: The method used is descriptive, which is a form of research used in a literature review with some data that has been found, a total of 6 articles applied, starting from the journal year used in 2020-2024. Results: The results in the literature review show that lavender aromatherapy is very effective in lowering a person's anxiety levels. Conclusion: Lavender aromatherapy can be used as a complementary nursing measure to lower a person's anxiety.